A “FRONTIER” OR A “SPHERE”: AN ESSAY ON A LEGACY OF EUROPEAN COLONIALISM - Zhou, Fangzheng (PEOPLE: International Journal of Social Sciences, 2018)
As a historical phenomenon, European colonialism has, from its beginning through the present day, a tremendous influence on the history of human beings, and has long been studied by students and scholars from all parts of the world. Traditional understandings of the motivations and impacts of European colonialism has focused on the economic, political, and religious areas, which, without doubts, are true and sound. However, the mentality behind the decisions and actions of colonialism was not commonly understood. This paper focus on exploring this type of predatory “frontier” mentality, as well as its antithesis the “sphere” mentality, through interpreting and understanding the human mind behind the various causes and consequences of European colonialism. Given the current global situation, the growth of the “sphere” mentality and the decline of its antithesis is likely to be the general trend as a product of the evolution of human civilization in the twenty first century. This shift in human mentality from competition to cooperation is the biggest legacy of European colonialism.